IMPLEMENTASI BUSINESS INTELLIGENCE DALAM MENGANALISIS DATA MENGGUNAKAN TABLEAU PADA PT GLOBAL BINTAN PERMATA - Guy Ritchie; Susanto Hariyanto (Komunitas Dosen Indonesia, 2023)
PT Global Bintan Permata is member group Yafindo (Batam, Indonesia) which is engaged in the distribution and import goods consumption and goods consumption throughout Indonesia . one _ business being run is distributing sugar _ throughout modern market and delivery some are via transportation and some are done in a manner independent . The target market namely the big modern market like Alfamart , Alfamidi , Indomarco , Indogrosir , Tiptop, and there is also a small modern market like Totalfruits , Grandlucky , etc. _ Of the many transactions made by the company this company _ This Still Not yet own Dashboard application for monitoring activity operations and transactions . So from it is needed something deep data visualization dashboard shape . Method used to data warehouse design is use method kimball nine-step technology. For the Extract, Transform and Load (ETL) process for data warehouse design using tools in the Pentaho Data Integration application , meanwhile For dashboard visualization is done with use the Tableau Public app . Result of application Tableau Public app is form generated data visualization dashboard reports containing information in form the data visualization it consists of from transaction and marketing data in 2021. Dashboard provides information For know How development sale both product and sales are also developing transactions with customers in 2021 later will become base in taking decisions required by management within PT Global Bintan Permata for help in the process of taking decision.